2011
DOI: 10.4304/tpls.1.10.1432-1436
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Language Learning Strategies and Gender among Primary School Students

Abstract: Abstract-Research on language learning strategies has been carried out extensively since mid 1990s in Malaysia. These studies have covered the language learning strategies among secondary and undergraduate students but not on primary school students. The main objective of the study was to identify and compare the language learning strategies used by male and female primary school students. Data was collected using a survey questionnaire with 60 students from two classes of primary 6, consisting of 30 male stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
3
9
1
Order By: Relevance
“…Therefore the null hypothesis is accepted. This result does not support the findings of Salahshour et al (2012); Kaur and Embi (2011) in which they reported that females used language learning strategies more frequently than males.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…Therefore the null hypothesis is accepted. This result does not support the findings of Salahshour et al (2012); Kaur and Embi (2011) in which they reported that females used language learning strategies more frequently than males.…”
Section: Resultscontrasting
confidence: 57%
“…A study was conducted by Kaur and Embi (2011) to identify and compare the language learning strategies used by male and female primary school students. For the purpose of this study a background information questionnaire and a bilingual Language Strategy Use Questionnaire were applied.…”
Section: B Taxonomy Of Language Learning Strategiesmentioning
confidence: 99%
“…In recent time, various studies (e.g. Aljuaid, 2010;Chilkiewicz, 2015;Fazle & Khan, 2012;Kaur & Embi, 2011;& Pineda, 2010) have investigated teachers' and learners' perception of the use of language learning strategies. However, none of these studies had compared the language learning strategies used by young learners and adolescent learners.…”
Section: Previous Studies On Language Learning Strategiesmentioning
confidence: 99%
“…For example, Zare (2010) found that the overall use of language learning strategies significantly varied according to gender. Beside that Kaur and Embi (2011) also found that there was a significant difference in the overall of strategies between male and female students. Female students tend to use overall language learning strategies more often than male students in learning English language.…”
Section: The Difference In Language Learning Strategies Use Due To Gementioning
confidence: 82%